Analysis of Strategy and Business in SME: Case Study From F&B Product, Bandung, Indonesia - Rizki, Aisha Dwi; Ranjana, Anandira Gusti; Safitri, Debi Dwi; Cantika, Maytama Rizki; Nurdin, Natashya Zahra; Jamiat, Nuslih (Manunggal Halim Jaya, 2025)
Micro, Small, and Medium Enterprises have contributed to Indonesia's significant economic turnover. Digitalization and the development of the times challenge UMKMs to enlarge their potential and portion of their business continuously. However, Berdikari maximizes many opportunities and potential to continue progressing and developing. Kenikmatan Duniawi is a UMKM from Bandung engaged in the F&B sector by selling bakery products. Kenikmatan Duniawi has been established since 2021, even though it has been established for 3 years, of course, Kenikmatan Duniawi still has many considerable challenges for its owners, such as limited human resources, marketing that is still passive, and many UMKM that sell Sourdough. This study aims to determine the business strategy needed by Kenikmatan Duniawi based on SWOT analysis. The variables in this study are SWOT and the SWOT matrix. This research uses qualitative methods, including data analysis techniques such as interviews, documentation, and field notes.